The Role of Parents and Environmental Conditions in the Incidence of Malaria in School-Aged Children in East Sumba Regency, Indonesia - Kareri Hara, Maria; Landudjama, Leni; To’o Jala Mulu, Servasius (Nurse Media Journal of Nursing, 2025)
Background: Malaria remains a major public health concern in eastern Indonesia, with East Nusa Tenggara Province ranking second in national malaria endemicity. In this region, East Sumba Regency is among the highest-burden districts, where school-aged children (5–14 years) account for 42.9% of reported cases and 2–3 new infections are recorded daily. Despite this high burden, limited research has examined how parental roles and environmental conditions contribute to malaria incidence in this vulnerable age group. Understanding these factors is critical for informing targeted prevention strategies.Purpose: This study aimed to examine the relationship between parental roles and environmental conditions with the incidence of malaria among school-aged children in East Sumba Regency, Indonesia.Methods: A cross-sectional quantitative study was conducted in January 2022 involving 120 school-aged children (grades 5 and 6) from an area in East Sumba Regency, selected through total sampling. Data were collected using validated, modified questionnaires measuring parental involvement and environmental conditions related to malaria risks. Descriptive statistics were used for univariate analysis, and Pearson’s Chi-square test was applied for bivariate analysis.Results: Among the respondents, 43 children (35.8%) had a history of malaria, while 77 (64.2%) had never experienced it. Poor parental roles were reported by 42.5% of participants, and 57.5% lived in substandard environmental conditions. Significant associations were found between parental roles (p=0.020) and environmental conditions (p=0.018) with the incidence of malaria.Conclusion: Parental roles and environmental conditions are significantly associated with the incidence of malaria among school-aged children in East Sumba. Strengthening parental involvement and improving environmental health can be effective strategies for reducing malaria transmission in endemic settings.